A newly recognised species of Cryptes Maskell 1892 (Hemiptera: Coccidae) from Western Australia - Lin, Yen-Po; Kondo, Takumasa; Kondo, Takumasa; Gullan, Penny J.; Cook, Lyn G. (Zootaxa, 2018)
Cryptes utzoni Lin, Kondo & Cook sp. n. (Hemiptera: Coccidae) is described based on adult female morphology and DNA sequences from mitochondrial and nuclear loci. This Australian endemic species was found on the stem of Acacia aneura (Fabaceae) in Western Australia. All phylogenetic analyses of three independent DNA loci show that C. utzoni is closely related to C. baccatus (Maskell), the type and only species of Cryptes Maskell, 1892. The adult female of C. utzoni is described and illustrated and a table is provided of the characters that differ among adult females of the two species of Cryptes now recognised (C. baccatus and C. utzoni) and a morphologically similar Western Australian species, Austrolichtensia hakearum (Fuller). There is deep genetic divergence in COI among samples of C. baccatus, suggesting the possibility of a species complex in this taxon.